Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1042/bj20141176
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AtMPK9 through autophosphorylation that makes it independent of the canonical MAPK cascades

Abstract: Mitogen activated protein kinases (MAPKs) are part of conserved signal transduction modules in eukaryotes that are typically organised into three-tiered kinase cascades. The activation of MAPKs in these pathways is fully dependent on the bisphosphorylation of the TXY motif in the T-loop by the pertinent dual-specificity MAPK kinases (MAPKKs). The plant AtMPK9 is a member of an atypical class of MAPKs. Representatives of this MAPK family have TDY phosphoacceptor site, a long C-terminal extension, and lack the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 37 publications
(40 reference statements)
3
15
0
Order By: Relevance
“…It was reported previously that MPK9 and MPK12 function downstream of ROS and modulate SLAC1 activity in guard cell ABA signaling (Jammes et al, 2009(Jammes et al, , 2011. Based on genetic and biochemical analyses, MKK4 and MKK5 are unable to activate MPK9 and MPK12 in vivo and in vitro (Asai et al, 2002;Lee et al, 2009;Nagy et al, 2015). As a result, MPK9/MPK12 and MPK3/MPK6 are likely to function as two independent MAPK cascades in stomatal movement.…”
Section: Discussionmentioning
confidence: 98%
“…It was reported previously that MPK9 and MPK12 function downstream of ROS and modulate SLAC1 activity in guard cell ABA signaling (Jammes et al, 2009(Jammes et al, , 2011. Based on genetic and biochemical analyses, MKK4 and MKK5 are unable to activate MPK9 and MPK12 in vivo and in vitro (Asai et al, 2002;Lee et al, 2009;Nagy et al, 2015). As a result, MPK9/MPK12 and MPK3/MPK6 are likely to function as two independent MAPK cascades in stomatal movement.…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that AtMPK12 but not AtMPK9 can interact with MAPK phosphatase IBR5 [162]. Recent research indicates that AtMPK9 can be activated by autophosphorylation that may be independent of any upstream MAPKKKs or MKKs [163]. Furthermore, AtMPK12 allele with an amino acid substitution alone could impair the ABA inhibition of opening [164].…”
Section: Regulation Of Stomatal Function By Mapk Cascades In Ros Signmentioning
confidence: 99%
“…Noteworthy, S 102 was followed by an alanine residue instead of a proline. Similarly, MPK9, another D‐type MPK, was able to autophosphorylate on S 464 that is also followed by an alanine (Nagy et al ., ). As the other TCP14 phosphoresidues detected were followed by various amino acids but proline, the sequences targeted by MPK8 and other D‐type MPKs might significantly diverge from the canonical [S/T‐P] motif, and the identification of additional substrates of these MPKs would help unravel their motif specificity.…”
Section: Discussionmentioning
confidence: 97%